2014
DOI: 10.7120/09627286.23.3.275
|View full text |Cite
|
Sign up to set email alerts
|

Docking the value of pigmeat? Prevalence and financial implications of welfare lesions in Irish slaughter pigs

Abstract: Expansion of the meat inspection process to incorporate animal-based welfare measurements could contribute towards significant improvements in pig (Sus scrofa domesticus) welfare and farm profitability. This study aimed to determine the prevalence of different welfare-related lesions on the carcase and their relationship with carcase condemnations (CC) and carcase weight (CW). The financial implications of losses associated with CC and CW reductions related to the welfare lesions were also estimated. Data on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
130
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(150 citation statements)
references
References 38 publications
15
130
3
2
Order By: Relevance
“…Tail lesion prevalence in the current study was approximately half the prevalence reported in previous studies examining tail lesions in pig herds on the island of Ireland (Harley et al, 2012a;Harley et al, 2014). It is possible that this reflects a decrease in the prevalence of tail lesions in pig herds on the island of Ireland.…”
Section: Discussioncontrasting
confidence: 42%
See 4 more Smart Citations
“…Tail lesion prevalence in the current study was approximately half the prevalence reported in previous studies examining tail lesions in pig herds on the island of Ireland (Harley et al, 2012a;Harley et al, 2014). It is possible that this reflects a decrease in the prevalence of tail lesions in pig herds on the island of Ireland.…”
Section: Discussioncontrasting
confidence: 42%
“…Some researchers argue that these processes could make welfare-related carcass damage difficult to detect (Taylor et al, 2010;Aaslyng et al, 2013). However, others suggest that this damage may be more detectable after these processes (Harley et al, 2014;Stärk et al, 2014). It appears that the current study is the first to actually investigate this in a controlled way.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations